Experimental investigation on Magnetorheological Damper’s characterization - Ferdaus, Mohammad Meftahul; Rashid, Muhammad Mahbubur; Muhammad, Hasibul hasan; Shanta, Mst. Nafisa Tamanna (Trans Tech Publications, Switzerland, 2015)
Magnetorheological (MR) damper is one of the most advanced application of semi active devices. Its use is increasing day by day due to its huge advantages and wide range of application. The force delivered by MR damper can be varied by changing the viscosity of its internal MR fluids. Till now no details experimental analysis has been accomplished by considering various parameters. In this paper a brief experimental analysis has been investigated with the help of Universal Testing Machine to characterize MR damper. To characterize accurately MR damper has been analyzed experimentally for different stroke length, stroke rate, stroke mode. From the experimental results it is seen that the force delivered by MR damper has a proportional relation with input excitation current, stroke length and stroke rate.